Decision Support System to Improve Employee Productivity Using the Simple Additive Weighting (SAW) Method Based on Java - Rivaldi Aziz Sudrajat; Susano, Adhi; Pinahayu, Ek Ajeng Rahmi (Edusight International Journal of Multidisciplinary Studies, 2024)
This research aims to develop a decision support system (DSS) to enchane employee productivity using the Simple Additive Weighting (SAW) method based on Java. The system is designed to criteria such as age, attendance, performance, and targets. The research method used in the development of this system include data collection through observation and interviews with employess, followed by analysis using the SAW method. The SAW method was chosen for its ability to provide accurate and easily understandable results by summing the weights of each normalized criterion. The system implementation is carried out using Java Netbeans, known for its advantages in designing a system tha is easy to understand. The result of this research show that the system can accurately provide information related to the citeria used within the company through the specified calculations. The SAW method can consider four main criteria: age, attendance, performance, and targets, thus allowing the employee selection process at PT. XYZ Karawang to be performed with higher accuracy and precision. Additionaly, the data related to these criteria can be well summarized and neatly organized within the application database.